Peran dan Kedudukan Perempuan dalam Keluarga Menurut Hukum Islam: Kajian Kritis Terhadap Praktik Kontemporer - Daharis, Ade (LITERATUS, 2023)
This research conducts a nuanced examination of women's roles within Islamic families by dissecting the intersection of Islamic doctrine and modern societal practices. Utilizing an in-depth qualitative literature review, this study scrutinizes the application of gender equality as postulated in Islamic jurisprudence vis-à-vis the evolving socio-economic milieu. The findings reveal that while Islamic law inherently endorses gender parity, its practical execution is often skewed by the interplay of cultural customs and localized traditions. Key insights point to specific cultural practices and regional interpretations of Islamic law that have historically marginalized women's roles in familial hierarchies. Examples include inheritance customs in certain regions that deviate from Quranic stipulations, as well as the societal expectations placed on women to forgo professional aspirations for domestic responsibilities. These cultural impositions are juxtaposed with the Islamic principles of equity, often leading to a dichotomous existence for women who strive to fulfill their roles within the family while adhering to their faith. The methodology encompasses a comparative analysis of canonical Islamic texts and field studies from diverse Islamic societies, providing a comprehensive perspective on the disparities between scriptural teachings and lived experiences. The study also interrogates the shifts in gender roles precipitated by increased access to education for women, resulting in a reconfiguration of traditional family structures and the emergence of new challenges. Policy implications drawn from this research underscore the necessity of educational reform and advocacy that promote the reconciliation of religious tenets with contemporary gender norms. The recommendations advocate for the integration of gender-sensitive pedagogy within religious education, as well as community outreach programs that aim to align societal perceptions with the egalitarian ethos of Islam. In essence, this research delineates a complex tapestry of faith, culture, and gender, offering a substantive foundation for strategies aimed at fostering gender equality and justice within Islamic families.